The Myths of Armenian «Velvet» Revolution - Melkonyan, Nvard; Asriyan, Elina (Bulletin of Yerevan University E: Philosophy, Psychology, 2018)
Political myths are used in politics as a form of communication between society and a political subject. The relevance of political myths grows in times of social crisis when society needs new, unifying symbols. Such symbols can be images of the Hero and Enemy, which were involved in the context of velvet revolution in Armenia in 2018. In addition to these symbols, the myth of the people's power was actualized too. That myth became the key message of the revolutionary movement in April in Armenia.
Keywords: myth, revolution, image, hero, enemy, target group